"The Masks We Wear": A Qualitative Study of Suicide in Australian Farmers. Issue 3 (10th January 2018) - Kunde, Lisa; Kõlves, Kairi; Kelly, Brian; Reddy, Prasuna; de Leo, Diego
Abstract: Purpose: Farmer suicide is a major public issue in Australia. Using the psychological autopsy method, this study aimed to examine the life and death circumstances of Australian male farmers who died by suicide through verbal reports from their close significant others. Methods: Individual semistructured interviews were conducted with 12 relatives of male farmers who had died by suicide in Queensland or New South Wales, Australia (2006‐2014). This study followed the COREQ checklist criteria for the reporting of qualitative research. Findings: Six interrelated themes were identified: (1) masculinity, (2) uncertainty and lack of control in farming, (3) feelings of failure in relationships and farming, (4) escalating health problems, (5) maladaptive coping, and (6) acquired capability with access to means. Conclusions: Effective clinical interventions, as well as suicide prevention strategies, need to consider the importance of 3 key issues in suicide among farmers: adherence to masculine norms and socialization; expectations of self in maintaining family traditions and occupation; and a male subtype of depression.